Farmers’ Knowledge of Soil Health Card and Constraints in its Use (Indian Journal of Extension Education, 2020)
Soil health and fertility is the representative for sustained high crop productivity and profitability of the farmers. Although soil testing is a regular feature of the Department of Agriculture Cooperation and Farmer’s Welfare but after the launch of Soil Health Card Scheme, soil testing is taken up on a mission mode. The study was undertaken to study the knowledge of farmers regarding the application of Soil Health Card issued under Soil Health Card Scheme and constraints faced by them in its use. Findings of the study revealed that majority of the beneficiaries had knowledge regarding ideal time for the collection of soil sample and collection of soil sample from the place where a heap of FYM is not placed. About 73 per cent of the beneficiaries were having knowledge regarding different macro nutrients displayed on SHC and majority of the respondents had knowledge regarding judicious use of fertilizers and various soil testing laboratories available for soil testing. Majority of the beneficiaries had medium level of overall knowledge regarding the application of SHC. Difficulty in operating internet to access soil health card portal, delay in receiving SHC and lack of mobile soil testing vans were major constraints faced by the farmers in the application of SHC.